EVALUASI PENGARUH LAPORAN KEUANGAN TERHADAP KEPUTUSAN INVESTASI: PENDEKATAN KUANTITATIF DENGAN ANALISIS REGRESI - ersi sisdianto; wardana, Syahla nabil (PT. Intelek Cendikiawan Nusantara, 2024)
Regression analysis and a quantitative approach are used in this study to assess how financial statements affect investment choices. Financial statements are regarded in the investment community as one of the primary determinants of investor choices. Accurate and transparent financial statements give investors crucial information about a company's performance and state, enabling them to make wiser investment choices. Financial statement information from a number of businesses listed between 2018 and 2022 on the Indonesia Stock Exchange (IDX) is used in this study. To examine the impact of independent variables, specifically financial ratios (liquidity, profitability, and solvency), on investment choices as indicated by stock prices and trading volume, multiple linear regression analysis is employed.Keywords: Financial Statements, Investment Decisions, Regression Analysis, Financial Ratios, Indonesia Stock Exchange